Immediate Impact of Percutaneous Transvenous Mitral Valve Commissurotomy (PTMC) on Right Ventricular Function - Kundu, SK; Majumder, AAS; Halder, D; Chakrovortty, SK; Khan, MR; Dutta, B; Karmoker, KK; Ahmed, M (Cardiovascular Journal, 2012)
Background: The aim of this study was to evaluate the immediate impact of Percutaneous Transvenous Mitral Commissurotomy (PTMC) on RV function in patients with mitral stenosis (MS). Methods: This study was conducted in the National Institute Cardiovascular Diseases, Dhaka for a period of one year starting from October 2008 to September 2009. A total of 50 consecutive patients (Case group) with mitral stenosis were selected after considering inclusion and exclusion criteria that subsequently undergone PTMC. The control group (n=50) consisted of age and sex matched healthy individual (having no ECG or echocardiographic evidence of structural or functional cardiovascular disease). Healthy control group was taken because there was no data about RV function in our population. Control group used to compare with baseline characteristics of case group. Results: Immediately after PTMC (24 to 48 hours) mitral valve area increased from 0.8± 0.1 to 2.0 ± 0.2 (p <0.001) and RV outflow tract fractional shortening (RVOTfs % ) increased from 54.9 ± 4.6 to 74.9 ± 4.8% (p <0.001). There was a significant decrease in systolic pulmonary artery pressure from 47.7 ± 7.9mmHg to 28.2 ± 5.9 mmHg (p <0.001), in the RV Tei index from 0.5 ± 0.1 to 0.3 ± 0.1 (p <0.001 ), in myocardial acceleration during isovolumic contraction (IVA) at the lateral tricuspid annulus from 0.4 ± 0.1 m/s² to 0.3 ± 0.0 m/s² (p <0.001). The RVEF (%) did not exhibit any significant change from pre-PTMC figure (p = 0.538). Conclusion: After successful PTMC the parameters of infundibular and global RV function as assessed by RVOTfs and Tei index showed significant improvement and significant decrease in RV contractility as assessed by IVA was observed. Further work using larger numbers of patients is needed to confirm our findings and to assess their utility in patient follow-up and management. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12205 Cardiovasc. j. 2012; 5(1): 3-11